Faecal parameters as biomarkers of the equine hindgut microbial ecosystem under dietary change. (9th January 2017) - Grimm, P.; Philippeau, C.; Julliand, V.
Abstract : Faeces could be used for evaluating the balance of the equine hindgut microbial ecosystem, which would offer a practical method for assessing gut health and how this relates to disease. However, previous studies concluded that faeces microbial ecosystem was not representative of the proximal hindgut (caecum and ventral colon). This study aimed to evaluate if variations of the faecal microbial ecosystem were similar to those observed in the proximal hindgut. Six horses, fistulated in the caecum and right ventral (RV) colon, were subjected to a gradual change of diet, from a 100% hay (high fibre) diet (2.2 DM kg/day per 100 kg BW) to a 57% hay+43% barley (high starch) diet (0.8 DM kg/day per 100 kg BW hay and 0.6 DM kg/day per 100 kg BW barley). The two diets were iso-energetic and fed over a 3-week trial period. Samples of digesta from the caecum, RV colon and faeces were collected two times on the 10th and 20th day of the trial, for each diet to assess the microbial ecosystem parameters by both classical culture technics and biochemical methods. The variations observed in the caecal and colonic bacterial composition (increase in total anaerobic, amylolytic and lactate-utilizing and decrease in cellulolytic bacteria concentrations) and microbial activity (changes in volatile fatty acids concentrations and increase in lactate concentrations) demonstrated that the hay+barley diet caused changes in the hindgut microbial ecosystem. Similar variations were observed in the faecal microbial ecosystem. Feeding the hay+barley diet resulted in higher concentrations of faecal lipopolysaccharides. The functional bacterial group concentrations (cellulolytics, amylolytics and lactate utilizers) were significantly correlated between caecum and faeces and between colon and faeces. From analyses of the metabolites produced from microbial activity, only valerate concentration in the caecum and the proportion of propionate were significantly correlated with the same parameters in the faeces. Results of the principal component analysis performed between all the caecal/faecal and colonic/faecal parameters revealed that the total anaerobic and cellulolytic bacteria concentrations, as well as valerate, l -lactate and lipopolysaccharide concentrations were strongly correlated with several microbial parameters in the caecum ( P <0.027; r >|0.45|) and in the colon ( P <0.013; r >|0.50|). This demonstrated that faecal samples and their bacterial analyses could be used to represent caecum and RV colon hindgut microbial ecosystem in terms of variations during a change from a high-fibre to a high-starch diet, and thus could be markers of particular interest to diagnostic proximal hindgut microbial disturbances.